A bibliometric and technical review of supplementary cementitious materials for 3D concrete printing: Research trends, current status, challenges, and future directions - Mahmood, Mir Zubayer; Aizat, Alias; Hasan, Kamrul (Springer, 2026)
3D concrete printing (3DCP) has become a revolutionary technology, but the dependence on Portland cement creates environmental problems, prompting the search for sustainable solutions. Although many studies have investigated individual supplementary cementitious materials (SCMs) in 3DCP, a structured evaluation that considers material chemistry, printability, performance, and sustainability is still lacking. Therefore, this research presents the role of SCMs in 3DCP, focusing on material performance, sustainability, and emerging research directions. The scope of this study includes research done from 2015 to 2024 on 3DCP-based SCMs. VOSviewer and R-based scientometric software were used for analysis of authors, publication trends, institutions, and keyword evolution, leading to a combined bibliometric and technical review. A technical review was undertaken to evaluate various mix design options, rheological characteristics, interlayer bonding, mechanical behaviour, and sustainability of using SCMs in 3DCP. These approaches position this study within the field of sustainable 3DCP, elaborating on ways to enhance environmental performance and identifying priorities for future studies. This review reveals an increase in research efforts, indicating that SCMs effectively reduce cement content, improve printability, accelerate the construction process, and achieve strength performance comparable to conventional mixes. Despite these favourable trends, several unresolved issues remain, such as standard testing procedures, long-term durability evaluations, and site-scale performance assessments. This review highlights the need to establish research priorities to address issues such as the optimisation of ternary mixture formulations, the use of predictive modelling software, and the development of regulatory frameworks to enable the widespread adoption of large-scale 3DCP technologies in the future.